The Effect of Cement Replacement Materials to the Hydration of Petroleum Sludge in OPC - Mohd Zain, Asna (2014)
The effect of cement replacement materials on hydration of solidified waste in ordinary Portland cement has been investigated based on initial setting time. Five cement replacement materials namely, rice husk ash, condensed silica fume, activated carbon, fly ash and meta kaolin were selected for solidified organic waste in the cement. The initial setting time was conducted with incorporation of 5 to 15 percent cement replacement materials at water to cement ratio of 0.45. The initial set of cement involves mainly the development of ettringite fibers and portlandite. Additions of CSF, FA and AC have delayed the initial setting time. The governing factors contributed to the delayed in setting time are the cement replacement materials, particle size and composition, which significantly retard development of ettringite fibers. 5 % MK and RHA tend to accelerate the setting with 138 and 150 minutes, accordingly as these binders have larger particle size.